Bicarbazoles: Systematic Structure–Property Investigations on a Series of Conjugated Carbazole Dimers - Kato, Shin-ichiro; Noguchi, Hiroto; Kobayashi, Atsushi; Yoshihara, Toshitada; Tobita, Seiji; Nakamura, Yosuke (Journal of organic chemistry, 2012)
A large series of conjugated carbazole dimers, namely bicarbazoles 1–12, were synthesized by Suzuki–Miyaura, Sonogashira, Hay, and McMurry coupling reactions. In 1–12, the two carbazole moieties are linked at the 1-, 2-, or 3-position directly or via an acetylenic or olefinic spacer. The structure–property relationships, particularly the effects of the conjugation connectivity and the π-conjugated spacers on the electronic, photophysical, and electrochemical properties of 1–12, were studied by extensive UV–vis and fluorescence spectroscopic measurements, cyclic voltammetry (CV), and theoretical calculations as well as X-ray crystallographic analyses. The connection at the 1-position of carbazole ensures high extent of π-conjugation, while that at the 3-position enhances the electron-donating ability. Both acetylenic and olefinic spacers allow the extension of π-conjugation, and the latter also causes the increase of the donor ability. Moreover, the structural variations were found to affect the fluorescence quantum yields significantly, which are up to 0.84.